First report of Phyllactinia guttata (Wallr.) Lév on Quercus infectoria Oliv in Syria - الجلاد رنا محمد (Latakia University Journal -Biological Sciences Series, 2020)
During field trips to some forests in several regions of Syria and during the months of October, November and December of 2019, the symptoms of powdery mildew have been observed on many Oak trees. After studying the phenotypic symptoms and microscopic examination of the physical structures of fungus /Chasmothecia-Fruiting bodies-, Ascocarps, Ascospores and conidia/ and comparing it with the specialized references indicates that Oak trees were infected in all studies areas with Microsphaera alphitoides and registration of infection for the first time with Phyllactinia guttata in the Albahloliya region of Lattakia Governorate and this is the first report of P. guttata in Syria.